Selection of the Use of Various Poverty Indicators in the Formulation of Development Policies in Papua Province 2002-2022 - Lesty, Anastasia Eka (AIBPM Publisher, 2023)
Poverty is a frequent topic of conversation. The purpose of this study is to examine the relationship between the poverty rate, the people living in poverty, the depth of the poverty index, and the severity of the poverty index in Papua Province from 2002 to 2022. Data analysis entails using descriptive analysis and correlation analysis techniques. While no clear association is found between the poverty rate indicator and the number of individuals living in poverty, a positive correlation exists between the poverty rate indicator and the poverty depth index. Additionally, there is a direct relationship between the poverty rate indicator and the poverty severity index, though with a low correlation coefficient. Conversely, no significant association is observed between the depth of the poverty index and the number of destitute individuals. Furthermore, a negative link is noted between the poverty severity index and the population of individuals living in poverty. Notably, a highly significant correlation exists between the depth and severity of the poverty index in Papua Province. The government of Papua Province should prioritize poverty reduction activities by selecting one of the four available alternatives. These tasks are required to achieve this requirement.Â Keywords: Number of Poor People; Poverty Depth Index; Poverty Rate; Poverty Severity Index